PROBLEM OF SCIENTIFIC WORKERS INFORMATION AND COMMUNICATION COMPETENCE - Ivanova, С.М. (Journal of Information Technologies in Education (ITE), 2013)
The article deals with the development of scientific workers information and communication competence. "Training program of scientific workers to work with electronic libraries" are proposed there. There are recommendations for teaching programs that will help increase the level of scientific workers information and communication competence, will learn the basic rules of scientific digital library, methods of modernization professional activity thanks to the technology and resources of scientific digital libraries.